PENDAMPINGAN MASYARAKAT SEBAGAI UPAYA KONSERVASI KAWASAN PESISIR DI NEGERI PASSO, KOTA AMBON - Wattimena, Cornelia Marietje Aneke (Universitas Pattimura, 2023)
Everyone should understand the importance of planting trees from an early age. Planting trees so far, without realizing it, is only a ceremony or a trivial activity without meaning. In fact, there are many benefits to planting trees, not only for humans but for all living things around them. The existence of trees is currently very important in overcoming pollution, both pollution due to motorized vehicles and pollution from factories, especially in densely populated cities. The following are the benefits, goals, and functions of planting trees for the survival of humans, animals, and the environment. The benefits of planting trees are that they can store rainwater and maintain water reserves in the soil. Trees have a mechanism for storing water in the soil. The roots of the tree will absorb water from the soil for their own needs in carrying out photosynthesis. The purpose of planting trees is to improve the function of the forest while at the same time improving the environment, Because this is an inheritance for posterity, we should plant as many trees as possible. The function of trees for air is that they will clean the air from pollutants and produce oxygen, which we will later inhale when we breathe. Trees also play a role in reducing the greenhouse effect caused by carbon dioxide gases in the atmosphere.